Therapeutic effect of Morus alba leaf extract and chlorogenic acid on inhibiting the progression of kidney disease - Fauzi, Ahmad; Titisari, Nurina; Noor, Mohd. Hezmee Mohd.; Azlan, Azrina; Hamzah, Hazilawati (Informa Healthcare, 2024)
It is well-established that Morus alba and its derivatives have been clinically proven to have antioxidant and anti-inflammatory properties. Although several studies have mentioned the beneficial effect of Morus alba on kidney disorders, the role of Morus alba in CKD still needs to be explored. Thus, this study investigated the effect of Morus alba and chlorogenic acid treatment on renal fibrosis in mice induced with unilateral urethral obstruction (UUO). Twenty-five Balb/c mice were randomly divided into five groups: the sham-operated group, the UUO untreated group, and the UUO treated with enalapril (ENA), Morus alba leaves extract (MLE) and chlorogenic acid (CGA) groups. Urine, blood, and organ samples were collected to evaluate urinalysis, haematology, biochemistry, and histopathology. The result indicated that the UUO group had significantly higher levels of creatinine (p < 0.001) and urea (p < 0.05), as well as hydronephrosis and urine crystal sedimentation (p < 0.05). In comparison to the UUO group, the MLE and CGA groups displayed improved urine profiles, ameliorated anaemia (p < 0.05), and urine crystals (p < 0.05). The administration of CGA also significantly reduced serum creatinine (p < 0.05) and protein-creatinine ratio (UPCr) levels. In addition, MLE and CGA could prevent hydronephrosis and delay renal damage, particularly in the dilation of Bowman’s space, tubular injury, loss of tubular epithelium, and cellular inflammation. In conclusion, Morus alba and CGA had a therapeutic effect in minimising the progression of renal damage. As a result, it can be promoted as a complementary renoprotective product based on natural products, as it has a potentially similar effect to enalapril.